2004
DOI: 10.1097/00005721-200405000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Care of the Patient With Preterm Premature Rupture of Membranes

Abstract: Preterm premature rupture of the membranes (PPROM) is diagnosed when rupture of the amniotic membranes occurs prior to the completion of the 36th week of gestation. PPROM accounts for 25% of all cases of premature rupture of the membranes and is responsible for 30%-40% of all preterm deliveries. In mothers diagnosed with PPROM without evidence of infection, active labor, or fetal compromise, the current standard of care is expectant management. The goal of expectant management is the prolongation of the pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Clinical management of pPROM before 34 weeks of gestation is generally expectant, with controversies sorrounding the use of amniocentesis, corticosteroids, and tocolytics. In women without signs of infection, the current standard of care is hospitalization and bed rest until there is evidence of ascending infection or documentation of fetal lung maturity [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical management of pPROM before 34 weeks of gestation is generally expectant, with controversies sorrounding the use of amniocentesis, corticosteroids, and tocolytics. In women without signs of infection, the current standard of care is hospitalization and bed rest until there is evidence of ascending infection or documentation of fetal lung maturity [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Primary intraamniotic subclinical infection is one of the main causes of pPROM and the early identification of such cases is necessary for choosing the proper mode of management [3, 5]. However, the number of methods of detecting subclinical infection is modest and limited.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of premature rupture of membranes (PROM) is reported to be between 6 and 10%, with almost 80% of these cases occurring at term 1 . Preterm premature rupture of membranes (pPROM) is diagnosed when rupture of amniotic membranes occurs prior to the completion of the 36th week of gestation 2 . It is one of the most common complications of pregnancy and accounts for nearly 30% of all preterm labors 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Preterm premature rupture of membranes (pPROM) is diagnosed when rupture of amniotic membranes occurs prior to the completion of the 36th week of gestation. 2 It is one of the most common complications of pregnancy and accounts for nearly 30% of all preterm labors. 3 In women with pPROM and without signs of infection, active labor or fetal distress, the current standard of care is expectant management with hospitalization and bed rest until there is evidence of ascending infection or documentation of fetal lung maturity.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, investigators found that many women reported consequences to being hospitalized, including stress, a loss of control over their pregnancy and familial obligations, boredom, and feeling burdensome for their families and health care professionals (Richter et al, 2007). In this setting, it is recommended that nurses help mothers to manage their stress by listening to and reassuring the mother that she did nothing wrong to cause the condition, by providing ongoing information about the mother’s and baby’s condition, and by involving parents in decision making (Stringer, Miesnik, Brown, Martz, & Macones, 2004). Other investigators described the critical role of spirituality in the women’s health and healing when faced with a high-risk pregnancy (Price et al, 2007).…”
Section: Introductionmentioning
confidence: 99%